Scenario-Guided Review of the Ghana Livestock Policy - Botchway, Vincent Ansah; Sam, Kingsley Odum; Karbo, Naaminong; Essegbey, George Owusu; Nutsukpo, Delali; Agyemang, Kingsley; Zougmoré, Robert B.; Partey, Samuel T. (Council for Scientific and Industrial Research, Ghana, 2016)
Climate change impacts are manifesting throughout the world and they are especially significant in developing countries, including Ghana, that are particularly vulnerable. The impacts of climate change are complex and uncertain in nature that the usual conventional planning often falls short to address. In agriculture in particular, planning should be purposively done to effectively address climate change impacts especially for the livestock sub-sector that always seem to be insufficiently catered for. To address the uncertainty of future developments in an adequate way, a methodology that acknowledges the uncertainty and complexity is essential. Scenario-building methodology is a tried-and-tested approach in that regard. It is based on systems science and seeks to recognize and explore uncertainty and complexity in the decision-makers’ context. In multi-stakeholder contexts, exploratory scenarios engage multiple legitimate perspectives involved in framing and addressing unclear challenges related to food security and the environment. This leads to an extensive overview of plausible futures, articulating complex interactions between socio-economic factors, political developments, climate change, and the global context. Policy making needs a methodology that appropriately delivers visionary options. For Ghana’s livestock sub-sector such visionary options are vital. And in order to produce a new and robust version of Ghana’s livestock policy, currently being finalized by the Ministry of Food and Agriculture (MoFA), MoFA in collaboration with the International Crop Research Institute for the Semi-Arid Tropics (ICRISAT), the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the Council for Scientific and Industrial Research (CSIR) has successfully organized a Three-Day Workshop from 13th to 15th July, 2016 at the Forest Hotel. The scenario-guided review workshop was conducted through a participatory approach which brought relevant stakeholders from the Government (MoFA, etc), academia, civil society and the private sector together to review the livestock policy. The CCAFS West Africa scenarios workshops informed the process in Ghana. In order to address specific issues in Ghana, these West Africa scenarios were downscaled and adapted to the level of Ghana by the Ghanaian stakeholders. These downscaled Ghana scenarios were then used for reviewing the livestock policy with the objective to produce a new, robust version in the face of future uncertainty. Dignitaries in attendance were Dr. Kwame Oppong-Anane, the Consultant for the Drafting of the Livestock Policy, who was the chairman for the workshop, Dr. E .K. Adu (Director, CSIR- ARI) who delivered the welcome address, Dr. Victor Agyeman (Director General, CSIR, Ghana), Dr. Robert Zougmore (CCAFS West Africa), and Mr. Kwamena Akorful (Director, APD , MoFA) who each delivered statements. Facilitators for the workshop included Dr. Samuel Partey, Dr. Karbo Naaminong, Dr.George Owusu Essegbey, Mr. Delali Nutsukpo, Mr. Vincent Ansah Botchway, Ms. Mavis Akuffobea and Kingsley Odum Sam who worked under the guidance of CCAFS’ Scenarios technical expert, Dr. Lucas Rutting, based at the Environmental Change Institute of the University of Oxford, UK.